SCIENTIFIC JUSTIFICATION OF THE EFFECT OF HAND-TO-HAND FIGHTING ON CARDIORESPIRATORY AND PSYCHOPHYSIOLOGICAL FUNCTIONAL INDICATORS IN MILITARY SCHOOLS (World Bulletin of Physical Education and Sports Science, 2026)
This article examines the impact of hand-to-hand combat training on the cardiorespiratory system and psychophysiological functional indicators in military cadets. The study evaluated the cardiovascular system's reactivity, external respiratory function, physical performance, and neurodynamic properties. The results of a 12-week experimental program demonstrated that hand-to-hand combat training enhances functional reserves, improves adaptive mechanisms, and enhances the performance of military cadets.
Keywords: Hand-to-hand combat, cadet, cardiorespiratory system, functional reserve, adaptation, and psychophysiological state.